2000
DOI: 10.1038/35013039
|View full text |Cite
|
Sign up to set email alerts
|

Slow differential rotation of the Earth's inner core indicated by temporal changes in scattering

Abstract: The finding that the Earth's inner core might be rotating faster than the mantle has important implications for our understanding of core processes, including the generation of the Earth's magnetic field. But the reported signal is subtle--a change of about 0.01 s per year in the separation of two seismic waves with differing paths through the core. Subsequent studies of such data have generally supported the conclusion that differential rotation exists, but the difficulty of accurately locating historic earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 19 publications
5
63
1
1
Order By: Relevance
“…Our result is also consistent with recent body wave studies that give eastward rotation rates between 0.15 and 0.25 • /yr (e.g. Creager, 2000;Vidale et al, 2000).…”
Section: Determining the Final Rotation Ratessupporting
confidence: 82%
See 1 more Smart Citation
“…Our result is also consistent with recent body wave studies that give eastward rotation rates between 0.15 and 0.25 • /yr (e.g. Creager, 2000;Vidale et al, 2000).…”
Section: Determining the Final Rotation Ratessupporting
confidence: 82%
“…Creager (2000) re-analyzed a large dataset of differential travel times and now sets the lower limit of the IC rotation rate to 0.15 • /yr which is actually consistent with his observations of 1997. This result would also be consistent with the small rate of 0.15 • /yr found in a study that investigated the time-dependence of inner core scattered waves generated by sources at the Novaya Zemlya test site and observed at the LASA (Large Aperture Seismic Array) in Montana (Vidale et al, 2000). Song (2000) re-analyzed his dataset in a joint inversion for inner core structure and superrotation and now finds that the superrotation is 0.6 • /yr which is less than 1 • /yr but still the highest recently published value.…”
Section: Introductionsupporting
confidence: 78%
“…The theory to be explored here is that the metallic solid inner core of the Earth is rotating with respect to the mantle, as has been confirmed by Song and Richards (1996) and Vidale et al (2000). This rotation maintains an angular velocity gradient across the outer core.…”
Section: Equations: "It Should Be Emphasised However That There Is mentioning
confidence: 93%
“…If the initial slope were greater than that of F i vs. d, it would certainly denote a stable offset from the Earth's spin axis. However, the estimate ω = 8.3 × 10 −11 rad s −1 (Vidale et al, 2000) gives…”
Section: Buoyancy Force (Outwards)mentioning
confidence: 99%
“…However, seismological studies have suggested structural and topographic complexities of the ICB. The existence of strong scattering from the inner core (Vidale et al 2000;Koper et al 2004) suggests heterogeneity at a scale length of tens of kilometers, which may be partly responsible for the attenuation of the waveforms passing through the inner core (Cormier et al 1998). The variability of pre-critical PKPcd (or PKiKP) amplitudes has been used to infer the mosaic structure of the ICB (Krasnoshchekov et al 2005), which includes patches of a thin partially liquid layer and patches of a sharp transition.…”
Section: Introductionmentioning
confidence: 99%